An Optimal Design of an Electromagnetic Actuation System towards a Large Homogeneous Magnetic Field and Accessible Workspace for Magnetic Manipulation - Laliphat Manamanchaiyaporn; Tiantian Xu; Xinyu Wu (Energies, 2020)
Untethered nano-/microrobots have been appealing to biomedical applications under magnetic guidance. Numerous actuation systems are specifically designed to generate either uniform or non-uniform fields which are unable to support all actuating mechanisms of magnetic robots. The size of their accessible space does not enable applications in life sciences (e.g., placing around human parts for tasks or an in vivo experiment in animals). Moreover, homogeneity of uniform magnetic fields is limited in a small region. Here, we propose an electromagnetic coil system that is optimally designed based on numerical simulation investigations to derestrict the mentioned constraints. The built-up system provides a large bore in which magnetic field generation by passing a 10 A current is strong enough for nano-/micromanipulation switchable between uniformity in a large-homogeneous region about 50-mm-wide along the x- and y-axes and 80-mm-wide along the z-axis, and with a non-uniformity of about 12 mT with 100 mT/m. It experimentally carries out potential and versatile controls to manipulate several commonly used microrobots that require a particular type of magnetic field to perform multi-DOF locomotion in diverse viscous environments. (e.g., helical propulsion by rotating magnetic field in the 3D-large workspace and in the complex network path, side-to-side sweeping-slip locomotion by oscillating fields, translation and rocking-slip locomotion by gradient-based fields). Besides, the system can be reproduced into any accessible space size regarding the square coil size to support diverse applications and guarantee the result in both uniformity of magnetic field in the large homogeneous region and a sufficiently strong gradient over the workspace.